1990
DOI: 10.1093/rheumatology/29.6.468
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Antibody Cross-Reactivity With Hla-Dr4+ve B-Lymphocytes. Basis of the Dr4 Associated Genetic Predisposition to Rheumatic Fever and Rheumatic Heart Disease?

Abstract: B-lymphocytes obtained from patients with either rheumatic fever or rheumatic heart disease and from normal subjects were reacted with serum obtained from rabbits immunized with streptococcal cell wall antigen. The presence of cytotoxicity was sought using an inverted phase microscope after differential uptake of eosin dye. The serum was found to be significantly more cytotoxic to HLA-DR4 containing cells of both patients and normals compared with DR4 negative cells (P less than 0.0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This theory is supported by a study in a population in which HLA-DR4 was associated with ARF. 69 The investigators found that antistreptococcal serum caused significantly increased toxicity to B lymphocytes bearing HLA-DR4 compared with DR4-negative lymphocytes, and they suggested that a strong antigenic similarity existed between HLA-DR4 and the streptococcal antigen, which led to defective antigen presentation by the HLA molecule ( Figure 2). This in turn could lead to aberrant cytokine production and ultimately antibody formation against proteins on valves, myocardium, brain, and joint tissue.…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory is supported by a study in a population in which HLA-DR4 was associated with ARF. 69 The investigators found that antistreptococcal serum caused significantly increased toxicity to B lymphocytes bearing HLA-DR4 compared with DR4-negative lymphocytes, and they suggested that a strong antigenic similarity existed between HLA-DR4 and the streptococcal antigen, which led to defective antigen presentation by the HLA molecule ( Figure 2). This in turn could lead to aberrant cytokine production and ultimately antibody formation against proteins on valves, myocardium, brain, and joint tissue.…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%
“…In some studies, results have been expressed as the percentage of B cells that stain positive for the D8/17 antigen. In others, a receiver operator curve or other method has been ) illustrates how antibodies may be central to the mechanism through which the HLA association is mediated, either through defective presentation by the HLA molecule because of antigenic similarity, 69 or through streptococcal antigens mimicking the HLA molecule. 70 This is proposed to lead to aberrant cytokine production, poor antigenic clearance, prolonged B cell stimulation and increased production of antibodies against the various tissues affected in ARF.…”
Section: B-cell Alloantigensmentioning
confidence: 99%
“…Outro estudo mostrou que linfócitos B provenientes de indivíduos com doença reumática cardíaca apresentavam citotoxicidade quando colocados em contato com anticorpos de coelhos imunizados com antígeno de parede bacteriana do estreptococo. A citotoxicidade foi muito maior com linfócitos B que possuíam o HLA-DR4 (46) . Analisando células humanas provenientes de uma população brasileira de 40 indivíduos com febre reumática foi observada importante associação entre antígenos de classe II do HLA com desenvolvimento de febre reumática e doença reumática cardíaca.…”
Section: Suscetibilidade Genéticaunclassified